IMPLIKASI TERBITNYA REGULASI TENTANG PERTIMAHAN TERHADAP DINAMIKA PERTAMBANGAN TIMAH INKONVENSIONAL DI PULAU BANGKA - Indra, Citra Asmara (Universitas Bangka Belitung, 2014)
Implication of the publication of the regulation of dynamics of tin mining on Bangka Island, it is most clearly visible are the rise of tin mining unconventional. The Central Government controls over commodities lead is so strong that they use their hands to do military protection. The local community is prohibited to mine, sell, even save them even one kilogram of matter. This condition is a precondition for the emergence of dissharmonsation in the management of lead in this area. Last issue about the rules of tin mining this regulation until now has never been resolved. So in a forum, all conflicts that erupted about tin mining will stop when the tin islands of Bangka Belitung Province have been exhausted.Keywords : Â Regulation, Tin mining, Bangka Island